Ten characteristics of high-quality planetary health education—Results from a qualitative study with educators, students as educators and study deans at medical schools in Germany - Simon, Johanna; Parisi, Sandra; Wabnitz, Katharina; Simmenroth, Anne; Schwienhorst-Stich, Eva-Maria (Frontiers in Public Health, 2023)
Aim: The climate and ecological crises are considered fundamental threats to human health. Healthcare workers in general and doctors in particular can contribute as change agents in mitigation and adaptation. Planetary health education (PHE) aims to harness this potential. This study explores perspectives among stakeholders involved in PHE at German medical schools on the characteristics of high-quality PHE and compares them to existing PHE frameworks. Methods: In 2021, we conducted a qualitative interview study with stakeholders from German medical schools involved in PHE. Three different groups were eligible: faculty members, medical students actively involved in PHE, and study deans of medical schools. Recruitment was performed through national PHE networks and snowball sampling. Thematic qualitative text analysis according to Kuckartz was used for the analysis. Results were systematically compared to three existing PHE frameworks. Results: A total of 20 participants (13 female) from 15 different medical schools were interviewed. Participants covered a wide range of professional backgrounds and experience in PHE education. The analysis revealed ten key themes: (1) Complexity and systems thinking, (2) inter- and transdisciplinarity, (3) ethical dimension, (4) responsibility of health professionals, (5) transformative competencies including practical skills, (6) space for reflection and resilience building, (7) special role of students, (8) need for curricular integration, (9) innovative and proven didactic methods, and (10) education as a driver of innovation. Six of our themes showed substantial overlap with existing PHE frameworks. Two of our themes were only mentioned in one of the frameworks, and two others were not explicitly mentioned. Few important elements of the frameworks did not emerge from our data. Conclusions: In the light of increased attention regarding the connections of the climate and ecological crises and health, our results can be useful for anyone working towards the integration of planetary health into medical schools´ or other health professions´ curricula and should be considered when designing and implementing new educational activities.